Pengaruh Penggunaan Media Pembelajaran Nearpod dan Kemandirian Belajar Terhadap Kemampuan Pemecahan Masalah Matematis - Alpi Mulyani; Dani Firmansyah (Program Studi Pendidikan Matematika, Universitas Majalengka, 2025)
This study aims to determine the effect of using Nearpod learning media and the level of learning independence on students' mathematical problem-solving abilities. The study uses a quantitative approach with a factorial experimental design, involving 30 students randomly selected from the research population. The instruments used consist of a mathematical problem-solving ability test in essay form and a Likert scale learning independence questionnaire. Data analysis was conducted using a Two-Way ANOVA test with the assistance of SPSS Statistics 25. The results of the study indicate that (1) there is a significant effect of the use of Nearpod learning media on students' mathematical problem-solving abilities, with higher average scores compared to other groups; (2) there was a significant effect of learning independence level on mathematical problem-solving ability, with students with high independence achieving better results; and (3) there was no significant interaction between the use of Nearpod learning media and learning independence level on mathematical problem-solving ability. These findings indicate that Nearpod and learning independence each contribute to students' abilities, but do not interactively influence one another.